Social recognition as a mechanism for children's identity restoration: a study of the porayamata practice in the pamona indigenous community - Asri Efriani Sauru; J.T. Lobby Loekmono; Izak Yohan Martriks Lattu; Tony Robert Christian Tampake (Journal of Counseling, Education and Society, 2026)
Children's identity within Indigenous communities is constructed not only through family relationships but also through social recognition and community acceptance. This study aims to examine how the Porayamata practice reconstructs the identity of ana ngkadoe within the Pamona Indigenous community and to explore its implications for social justice counseling. The study employed a qualitative approach with a critical ethnographic design, utilizing in-depth interviews, participant observation, and document analysis. The findings reveal that ana ngkadoe experience limited recognition within the kinship system, which affects their social standing. Through the involvement of families, the Dewan Adat, customary symbols, and community recognition, Porayamata reconstructs children's identities as legitimate members of both the family and the broader community. These findings suggest that identity restoration requires institutionalized social recognition embedded in cultural practices, thereby extending the perspective of social justice counseling, which has traditionally focused primarily on individual-level change.